Goat milk increases gastric emptying and alters caecal short chain fatty acid profile compared with cow milk in healthy rats. Issue 10 (22nd September 2020) - Dalziel, Julie E.; Dunstan, Kelly E.; Dewhurst, Hilary; Van Gendt, Melanie; Young, Wayne; Carpenter, Elizabeth
Abstract : Goat and cow milk share similar protein and lipid content, yet goat milk forms softer curds during stomach digestion. Abstract : Goat and cow milk share similar protein and lipid content, yet goat milk forms softer curds during stomach digestion. This has been assumed to hasten gastric emptying (GE) on consumption of goat milk compared with cow milk, although there is no direct evidence for this. We hypothesised that goat milk would increase GE and gastrointestinal transit compared with cow milk and alter short-chain fatty acid (SCFA) profiles. Ten week old rats were provided with a non-dairy diet and goat milk, cow milk, or water, ad libitum for two weeks. On day 14, X-ray imaging tracked the transit of metallic beads in vivo over 15 h. SCFA analysis of the caecal content was carried out post-mortem. Goat milk consumption increased GE compared with cow milk and controls, whereas colonic transit was slowed for both milk consuming groups. Goat milk altered the SCFA profile compared to controls. In particular, acetic and propionic acids in the caecum were present at a higher concentration in goat milk-fed rats. There was no difference between the SCFA profiles of cow milk and control animals. The more rapid gastric emptying conferred by goat milk supplementation provides evidence for improved digestibility. The slower colonic transit by both milks was associated with similar changes in motility associated with SCFA that suggest altered carbohydrate fermentation and lower levels of amino acid fermentation in the caecum.